INTRODUKTION TIL VOLDENS ANTROPOLOGI: Fra erfaring til fællesskab - Vigh, Henrik E. (Tidsskriftet Antropologi, 2002)
The article positions the different anthropological approaches to violence on a continuum from the phenomenological to the sociological analysis. It argues that anthropological works on violence are crystallized around either the experiential aspects of violence or the phenomenon’s ability to create, maintain and consolidate social communities. Yet, in conclusion it offers a perspective, which might be able to combine the different analythical avenues, arguing that the different points of departure intersect as violence creates communities of experience.